A comparative analysis of milk sectors - Nairobi, Kathmandu and Santa Cruz: Opportunities for pro-poor policies - Anderson, S.; Rushton, Jonathan; Tulachan, P.M.; Staal, Steven J.; Herrero, Mario (Cambridge University Press, 2004)
The paper presents the main findings of a set of comparative milk sector surveys carried out in Kathmandu (Nepal), Nairobi (Kenya) and Santa Cruz (Bolivia). The surveys assessed changes in demand, supply and marketing of milk and milk products over a ten to fifteen year period to 2001. The paper considers demand for milk and milk products, changes in milk supply and trading pathways, the policy frameworks, changes in demand and market share, and growth in the sector and poverty reduction. The policy implications for propoor development of the milk sector are discussed.